2024
DOI: 10.1073/pnas.2319686121
|View full text |Cite
|
Sign up to set email alerts
|

Orphan lysosomal solute carrier MFSD1 facilitates highly selective dipeptide transport

Danila Boytsov,
Gregor M. Madej,
Georg Horn
et al.

Abstract: Orphan solute carrier (SLC) represents a group of membrane transporters whose exact functions and substrate specificities are not known. Elucidating the function and regulation of orphan SLC transporters is not only crucial for advancing our knowledge of cellular and molecular biology but can potentially lead to the development of new therapeutic strategies. Here, we provide evidence for the biological function of a ubiquitous orphan lysosomal SLC, the Major Facilitator Superfamily Domain-containing Protein 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…During the revision of our manuscript, another study identified MFSD1 as a lysosomal dipeptide uniporter based on the accumulation of dipeptides with at least one cationic residue in MFSD1-defective lysosomes and the electrogenic transport of such dipeptides 65 . The authors concluded that MFSD1 is highly specific for this subset of dipeptides.…”
Section: Discussionmentioning
confidence: 99%
“…During the revision of our manuscript, another study identified MFSD1 as a lysosomal dipeptide uniporter based on the accumulation of dipeptides with at least one cationic residue in MFSD1-defective lysosomes and the electrogenic transport of such dipeptides 65 . The authors concluded that MFSD1 is highly specific for this subset of dipeptides.…”
Section: Discussionmentioning
confidence: 99%